Greenland [in "State of the Climate in 2010"] - Box, J. E.; Ahlstrøm, A.; Cappelen, J.; Fettweis, Xavier; Decker, D.; Mote, T.; van As, D.; van de Wal, R. S. W.; Vinther, B.; Wahr, J. (American Meteorological Society, 2011)
peer reviewed Record warm air temperatures were observed over Greenland in 2010. This included the warmest year on record for Greenland's capital, Nuuk, in at least 138 years. The duration of the melt period on Greenland’s inland ice sheet was exceptional, being 1 month longer than the average over the past 30 years, and led to an extended period of amplified summer melt. All of the additional melt water very likely contributing to a faster rate of crevasse widening. Glacier loss along the Greenland margins was also exceptional in 2010, with the largest single glacier area loss (110 square miles, at Petermann glacier) equivalent to an area four times that of Manhattan Island. There is now no doubt that Greenland ice losses have not just increased above past decades, but have accelerated. The implication is that sea level rise projections will again need to be revised upward.